2018
DOI: 10.1080/00016357.2018.1521005
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory profile of chronic apical periodontitis: a literature review

Abstract: Apical periodontitis caused by root canal infection is the most frequent pathological lesion in the jaws, mainly manifested as periapical granulomas and cysts. Understanding of the formation and progression of apical periodontitis as well as the identification of inflammatory biomarkers can help increase the knowledge of pathogenic mechanisms, improve the diagnosis and provide support for different therapeutic strategies. The objective of the present article is to review inflammatory biomarkers such as cytokin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
142
0
13

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 160 publications
(158 citation statements)
references
References 85 publications
3
142
0
13
Order By: Relevance
“…On the other hand, a cell culture study demonstrated that the RANK and RANKL factors are not sufficient for the firm and static union between osteoblasts and osteoclasts and that the ICAM‐1/LFA molecules are necessary to the effective adhesion between these cells during the osteoclastogenesis (Okada et al ). However, those present in vivo findings confirm the requirement of RANKL expressed on osteoblasts for osteoclasts maturation and the crucial involvement of the RANK and RANKL in periapical lesion development, as previously described (Vernal et al , Bezerra da Silva et al , Braz‐Silva et al , Francisconi et al . , Howait et al , Jakovljevic et al ).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…On the other hand, a cell culture study demonstrated that the RANK and RANKL factors are not sufficient for the firm and static union between osteoblasts and osteoclasts and that the ICAM‐1/LFA molecules are necessary to the effective adhesion between these cells during the osteoclastogenesis (Okada et al ). However, those present in vivo findings confirm the requirement of RANKL expressed on osteoblasts for osteoclasts maturation and the crucial involvement of the RANK and RANKL in periapical lesion development, as previously described (Vernal et al , Bezerra da Silva et al , Braz‐Silva et al , Francisconi et al . , Howait et al , Jakovljevic et al ).…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, a lower level of INF‐γ and higher level of IL‐10 in the ICAM‐1 KO mice was observed, while the expression of TNF‐α and OPG was equal to both groups. Although the main cytokines secreted by neutrophils are IL‐1, IL‐6 and TNF‐α (Márton & Kiss , Reinke & Sorg ), the pathogenesis of the biochemical network is not so obvious and occurs in a very complex and dynamic way (Braz‐Silva et al ). These cytokines are also produced by other inflammatory cells and show different behaviours, depending on the immunopathological micro‐environment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…, Braz‐Silva et al . ). Cytokines play an important role in innate and adaptive immunity and have a substantial role in managing the orientation, intensity and persistence of the inflammatory reaction (Roescher et al .…”
Section: Introductionmentioning
confidence: 97%
“…Chronic inflammatory lesions and destruction of alveolar bone structures are the result of the failure of host defence mechanisms to eradicate infection ). Although many experimental and clinical studies have been reported over the past decades to explore the pathogenesis and much is already known about the process, the exact role of immune cells, cytokines and other inflammatory mediators associated with the persistence and resolution of periapical lesions (PLs) is not completely understood (Marton & Kiss 2000, Nair 2004, Belibasakis et al 2013, Braz-Silva et al 2018. Cytokines play an important role in innate and adaptive immunity and have a substantial role in managing the orientation, intensity and persistence of the inflammatory reaction (Roescher et al 2009).…”
Section: Introductionmentioning
confidence: 99%